ROMANIAN VEGETABLE SECTOR A STUDY ON ITS CURRENT DEVELOPMENT - Cornelia ALBOIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The accession to the European Union has not brought about significant structural changes of the vegetables chain, this continuing to be highly fragmented, with an extremely great number of individual producers (over 85%), a relatively small number of industrial processors with high concentration level, and a well-developed retail sector that has significantly grown recently. The low organization level of vegetable farmers into producer groups/organizations/cooperatives completes this picture and reveals a reduced level of integration and contractualization. In these conditions, the question is how well-prepared the vegetable sector is to cope with the consequences of a possible accession to the euro area.